A Clinico-epidemiological Profile of Patients with Alopecia Areata: A Hospital-Based Cross-Sectional Study - Maharjan, Rupak; Karki, Alina (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Alopecia areata is one of the common types of non-cicatricial alopecia. It is considered an autoimmune disorder and effects hair bearing areas like scalp, eyebrows and beard. It also carries psychological burden. This study aimed to evaluate clinico-epidemiological profile of patients diagnosed with alopecia areata attending the dermatology outpatient department of a tertiary care center. Methods: A cross-sectional study was conducted from 1st Jan 2025 to 30th June 2025. after clearance from Institutional Review Committee (Reference number: NAPFH-033/2024) of the hospital. Data on patient demographics, clinical diagnosis and examination findings were collected on preformed proforma and entered in Statistical Package for the Social Sciences version 21. Descriptive statistics were used for analyses. Results: In our study, 52 cases were diagnosed with alopecia areata during the study period, out of which 40 (76.93%) were males and 12 (23.07%) were females with male to female ratio of 3.3:1. The majority of patients belonged to the 31–40 years age group, accounting for 24 (46.20%) cases. Most patients, 46 (88.50%), were asymptomatic, and the duration of the disease was less than 3 months in 43 (82.70%) cases. The scalp was the most commonly involved site in 42 (80.80%) cases, and patchy alopecia was the predominant pattern observed in 43 (82.70%) cases. Nail changes were present in 11 (21.20%) cases. Conclusions: In our study, Alopecia areata was more common in males. Scalp was predominantly involved site and patchy hair loss was the most common pattern observed. Early recognition, treatment and screening for other associated diseases is required for proper management of this condition.